Validation of the Worry Emotionality-Junior Scale (WE-J) for the assessment of the performance anxiety in primary school pupils in grades 3-5 - Di Vita, Alessandro; Di Martino, Valeria (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2024)
Performance anxiety in educational settings poses a significant challenge to students’ well-being and achievement, with potential long-term implications for their academic and personal development. The need for appropriate assessment tools for primary school children has led to the development of the test “Worry Emotionality-Junior” (WE-J), specifically adapted to measure performance anxiety in students aged 8 to 10 years. This study aims to validate the WE-J on a sample of 252 Italian students, with the objective of confirming its factor structure. The ultimate goal is to provide a valid and reliable instrument that can be used in primary schools to identify early on children who might benefit from targeted interventions for managing performance anxiety, thus contributing to their academic success and overall well-being.